FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MENGAKSES INTERNET TERHADAP AKSES SITUS PORNOGRAFI PADA REMAJA AWAL (12-15 TAHUN) DI SMP KECAMATAN SEMARANG BARAT - Intan Hardian Putri; Syamsulhuda B. Mustofa; Novia Handayani (Jurnal Kesehatan Masyarakat (Undip), 2020)
Adolescence is a period of rapid growth and development of physically, psychological and intellectually. Currently, it is not difficult to found the internet, especially among adolescents. The use of the internet is increasingly massive carries several implications that effect, positive or negative. This study was to analyze the behavior of accessing the Internet to access pornography sites in early adolescence (12-15 years) in the Junior High School District of West Semarang. This research has a quantitative research with the cross-sectional approach. Samples were selected using random sampling and sample proportions. This study used univariate and bivariate analysis using the Chi-square test. Results of univariate tests showed that more than half of the respondents were early puberty age group (52.2%), male (54.3%), good knowledge (53.2%), good attitude (51.1%), availability of internet facilities (64.9%), availability of device support (69.1%), lack of parental supervision (64.9%) and good influence of peers (53.2%). Variables related to the behavior of accessing pornography among others: Internet facilities (p = 0.017), availability of device support (p = 0.025), parental supervision (p = 0.017). Most of the respondents had access to pornography through the Internet amounted to 61.7%. Giving education about reproductive health and education sexuality is necessary to prevent the behavior of accessing pornography via the Internet among teenagers